2021
DOI: 10.1089/pmr.2021.0041
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Effect of Palliative Radiation Therapy in Preventing Blood Transfusions from Bleeding Occurring within Advanced Gastric Cancer

Abstract: Purpose: To report the hemostatic effects of palliative radiation therapy (RT) for the prevention of blood transfusions (BT) in patients with advanced gastric cancer (AGC). Methods and Materials: Twenty-eight patients who received palliative three-dimensional conformal RT for hemostasis of gastric bleeding were retrospectively assessed in a study conducted in Japan. The median follow-up was 143.5 days. Changes in hemoglobin (Hb) levels were compared at the beginning of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…Although some studies (11,12,17) have shown that radiotherapy is an effective method for bleeding, our data also shows the positive contribution of palliative RT on pain relief. In a series of 115 patients, Tey et al (9) reported that 80.6% of patients had bleeding control, 45.5% had pain control, and 51.2% had obstruction palliation with palliative RT in the metastatic and nonmetastatic patient group.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Although some studies (11,12,17) have shown that radiotherapy is an effective method for bleeding, our data also shows the positive contribution of palliative RT on pain relief. In a series of 115 patients, Tey et al (9) reported that 80.6% of patients had bleeding control, 45.5% had pain control, and 51.2% had obstruction palliation with palliative RT in the metastatic and nonmetastatic patient group.…”
Section: Discussioncontrasting
confidence: 49%
“…The total applied radiation dose also seems to have a role in outcomes. In the study of Mitsuashi et al (12) from Japan, where the incidence of gastric cancer is high, survival analysis was performed according to palliative RT dose.…”
Section: Discussionmentioning
confidence: 99%
“…All but one of the published studies regarding the use of radiation therapy for the management of bleeding secondary to AGC was a retrospective case series or case-control study, with only one non-randomized clinical trial intervention studied (16)(17)(18)(19)(20)(21)(22)(24)(25)(26)(28)(29)(30)(31)39). The most common treatment regimen was 30 Gy in 10 fractions ranging from a single 8 Gy fraction dose to 42 Gy over 20 fractions.…”
Section: Radiationmentioning
confidence: 99%
“…Palliative radiotherapy has emerged as a crucial therapeutic option for managing advanced HNSCC, particularly when curative interventions may not be feasible or suitable (9, 10). Palliative radiotherapy also offers a rationale for tumor shrinkage, hemostasis, and pain relief (11,12).Accordingly, in this study, we aimed to investigate the survival outcomes of patients with HNSCC undergoing palliative radiotherapy, considering specific challenges and factors associated with older age, and offer valuable insights into the appropriate use of palliative radiotherapy in these patients. Ultimately, the results will contribute to making 46…”
mentioning
confidence: 99%
“…Palliative radiotherapy has emerged as a crucial therapeutic option for managing advanced HNSCC, particularly when curative interventions may not be feasible or suitable (9, 10). Palliative radiotherapy also offers a rationale for tumor shrinkage, hemostasis, and pain relief (11,12).…”
mentioning
confidence: 99%